Development of Learning Cycle 5E Practical Instructions on Acid-Base Titration Using Natural pH Indicators Based on Green Chemistry - Apriliany Kartika Jani; Moersilah Moersilah (Scientia Publica Media, 2024)
This research aims to produce a learning media product in the form of a practical guide for the 5E learning cycle on acid-base titration material using natural pH indicators based on green chemistry that is valid and practical. The type of research used is Research and Development (R&D) with the Borg and Gall model using a descriptive quantitative method. The study was conducted from November 2021 to August 2022 at SMA N 53 Jakarta with 91 student respondents, eight teachers, three subject matter and language experts, and three media experts. The practical guide is equipped with a barcode to facilitate students’ access to videos, additional materials, and evaluation questions. The research results show that the pH range of the Red Shoot leaf extract is 2-5 with a color change from pink to yellow and 6-14 with a color change from yellow to brick red. The feasibility test results of the practical guide by the experts showed an average percentage of 85% for subject matter and language experts and 88% for media experts. The reliability test from the experts was categorized as “Very Reliable” with a value of 0.93 for both subject matter and language experts and media experts. The student trial results showed an average of 80% on a small scale and 90% on a large scale. The teacher trial results showed an average of 95% on a small scale. The trial results conclude that the practical guide for the 5E learning cycle on acid-base titration material using natural pH indicators based on green chemistry has met the criteria of “Very Good” and is suitable as a learning media. The attractive, innovative, and creative acid-base titration learning can use this practical guide as learning media.